Old English literature and the Old Testament - Fox, Michael, 1967-; Sharma, Manish, 1973- (Toronto [Ont.] : University of Toronto Press, 2012)
"It would be difficult to overestimate the importance of the Bible in the medieval world. For the Anglo-Saxons, literary culture emerged from sustained and intensive biblical study. Further, at least to judge from the Old English texts which survive, the Old Testament was the primary influence, both in terms of content and modes of interpretation. Though the Old Testament was only partially translated into Old English, recent studies have shown how completely interconnected Anglo-Latin and Old English literary traditions are.
Old English Literature and the Old Testament considers the importance of the Old Testament from a variety of disciplinary perspectives, from comparative to intertextual and historical. Though the essays focus on individual works, authors, or trends, including the Interrogationes Sigewulfi, Genesis A, and Daniel, each ultimately speaks to the vernacular corpus as a whole, suggesting approaches and methodologies for further study."--Pub. desc.
""The City as Speaker of the Old Testament in Andreas""""Cyningas sigefÃ?ste Ã?urh God: Contributions from Anglo-Saxon England to Early Advocacy for Ã?lÃ¡fr Haraldsson""; ""Happiness and the Psalms""; ""The Old English Kentish Psalm and Polysystems Theory""; ""Bibliography""; ""Index""; ""A""; ""B""; ""C""; ""D""; ""E""; ""F""; ""G""; ""H""; ""I""; ""J""; ""K""; ""L""; ""M""; ""N""; ""O""; ""P""; ""R""; ""S""; ""T""; ""U""; ""V""; ""W""; ""Y""
Includes bibliographical references and index.
English.
Committed to retain
JSTOR
Keywords: Bible -- In literature; Bible; Bibel; Bibeln; English literature -- Old English, ca. 450-1100 -- History and criticism; Christian literature, English (Old) -- History and criticism; Christianity and literature -- England -- History -- To 1500.; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Littérature chrétienne anglaise (vieil anglais) -- Histoire et critique; Bible dans la littérature.; Christianisme et littérature -- Angleterre -- Histoire -- Jusqu'à 1500.; LITERARY CRITICISM -- Medieval; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Christian literature, English (Old); Christianity and literature; English literature -- Old English; Literature; England; Altenglisch; Literatur; Rezeption; Rezeption; Altenglisch; Literatur; Bibliska motiv i litteraturen; Fornengelsk litteratur -- historia; Engelsk religiös litteratur -- forntiden -- medeltiden; To 1500; Criticism, interpretation, etc; History